Calibration-Free WMS Using a cw-DFB-QCL, a VCSEL, and an Edge-Emitting DFB Laser With In-Situ Real-Time Laser Parameter Characterization - Abhishek Upadhyay; David Wilson; Michael Lengden; Arup L. Chakraborty; George Stewart; Walter Johnstone (IEEE Photonics Journal)
This paper presents a detailed experimental wavelength modulation spectroscopy approach and demonstrates its applicability to various types of semiconductor lasers in the near infrared and mid-infrared. A 5250 nm continuous-wave distributed feedback quantum cascade laser, a 2004 nm vertical cavity surface emitting laser, and a 1650 nm distributed feedback edge-emitting laser are used to extract the concentration and pressure values of nitric oxide, carbon dioxide, and methane, respectively, using the $2f$ wavelength modulation spectroscopy (WMS) technique under controlled conditions. The generality of the technique is demonstrated by extending it to $3f$ WMS for the three different kinds of lasers used in this study. The methodology required to provide in-situ real-time measurements of both gas parameters and operating characteristics of the laser are described in detail. Finally, the advantages and limitations of the technique are discussed in view of the fact that the characteristic behavior of the laser sources is significantly different. We specifically discuss the issue of targeting non-absorbing wavelength regions and the choice of modulation frequency and modulation amplitude of the laser, as well as the choice of the detection harmonic.